Odpowiedź :
Odpowiedź:
zad. 12
I [tex]3-2\frac{1}{3}+1\frac{2}{3}=4\frac{2}{3}-2\frac{1}{3}=2\frac{1}{3}[/tex]
J [tex]4\frac{2}{3}+5\frac{1}{3}+8\frac{2}{3}=17\frac{5}{3}=18\frac{2}{3}[/tex]
Ń [tex]2+2\frac{2}{5}+1\frac{4}{5}=5\frac{6}{5}=6\frac{1}{5}[/tex]
K [tex]2\frac{3}{5}+0+2\frac{4}{5}=4 \frac{7}{5}=5\frac{2}{5}[/tex]
S [tex]5\frac{1}{2}-2\frac{1}{2}+3 =3+3=6[/tex]
R [tex]6\frac{4}{8}+5\frac{5}{8}-5\frac{2}{8}=6\frac{4}{8}+\frac{3}{8}=6\frac{7}{8}[/tex]
Z [tex]4\frac{4}{5}+5\frac{3}{5}-2\frac{2}{5}=9\frac{7}{5}-2\frac{2}{5}=10\frac{2}{5}-2\frac{2}{5}=8[/tex]
O [tex]4\frac{5}{8}-2\frac{5}{8}+4\frac{2}{8}=2+4\frac{2}{8}=6\frac{2}{8}[/tex]
Ó [tex]5\frac{1}{4}+4\frac{1}{4}+3\frac{3}{4}=12\frac{5}{4}=13\frac{1}{4}[/tex]
E [tex]6\frac{2}{3}-2\frac{1}{3}+3\frac{1}{3}=4\frac{1}{3}+3\frac{1}{3}=7\frac{2}{3}[/tex]
W [tex]2\frac{4}{10}+6\frac{7}{10}-2\frac{1}{10}=8\frac{11}{10}-2\frac{1}{10}=9\frac{1}{10}-2\frac{1}{10}=7[/tex]
F [tex]8\frac{4}{7}-3\frac{2}{7}+1\frac{6}{7}=5\frac{2}{7}+1\frac{6}{7}=6\frac{8}{7}=7\frac{1}{7}[/tex]
LICZBA: [tex]18\frac{2}{3}[/tex] [tex]13\frac{1}{4}[/tex] 8 [tex]7\frac{2}{3}[/tex] [tex]7\frac{1}{7}[/tex] 7 [tex]6\frac{7}{8}[/tex] [tex]6\frac{2}{8}[/tex] [tex]6\frac{1}{5}[/tex] 6 [tex]5\frac{2}{5}[/tex] [tex]2\frac{1}{3}[/tex]
LITERA: J Ó Z E F W R O Ń S K I
Szczegółowe wyjaśnienie: